Temptation at every corner: exploring public perceptions of food cues and policy support for governmental food cue regulation in outdoor public spaces - Tamika M. Wopereis; Sanne K. Djojosoeparto; Frédérique C. Rongen; Sanne C. Peeters; Emely de Vet; Maartje P. Poelman (BMC Medicine)
Abstract Background Unhealthy visual food cues in outdoor public spaces are external drivers of unhealthy diets. Food cues are visible situations associated with food-related memories. This study aimed to gain insight into the (un)healthy food cues residents notice in outdoor public spaces in Dutch municipalities. It also aimed to explore residents’ perceptions of food cues’ influence on eating behaviour to gain insight into the acceptability of food cues and support for governmental food cue regulation. Methods An exploratory study was conducted among 101 adults who photographed outdoor visual food cues in their municipality and answered survey questions about the food cues using a bespoke app (‘myfoodenvironment’). Participant and food cue characteristics were analysed. Associations between those characteristics, perceived influence on eating behaviour, acceptability of food cues and support for regulation were analysed. Results Participants took 461 photographs of food cues. Most food cues visualised food (73.8%), 54.4% of which showed only unhealthy food. Food cues photographed by participants with a high level of education and those located near a food service outlet were more often perceived as stimulating others to eat compared to those photographed by participants with a middle education level and located near a food store or along the road (Fisher’s exact test: p < 0.001 and p = 0.001, respectively). For most photographs, participants found the presence of food cues acceptable and were opposed to governmental cue regulation. However, when food cues visualised healthy food, they were more likely to be found acceptable than when visualising unhealthy food (χ 2 (4; N = 333) = 16.955; p = 0.002). Besides, when food cues visualised unhealthy food, participants were less likely to oppose governmental regulation of those types of cues, than when visualising healthy food (Fisher’s exact test: p = 0.002). Conclusions Unhealthy food cues in outdoor public spaces were predominantly photographed by the participants. Yet, for most photographs, participants found the food cues acceptable and opposed governmental food cue regulation, although acceptance was higher for healthy food cues and opposition was lower for unhealthy food cues. These findings can serve as input for policymakers to develop governmental food cue regulations that may gain public support.